DETERMINATION OF THE CHEMICAL AND GENETIC DIFFERENCES OF LAURUS COLLECTED FROM THREE DIFFERENT GEOGRAPHIC AND CLIMATIC AREAS IN LEBANON - Chmit Mohammad Said; Kanaan Hussein (European Scientific Journal, ESJ, 2014)
Laurus (Lauraceae) is growing in many warm regions of the world, particularly in southern Europe and around the shores of the Mediterranean Sea, including Lebanon. The aim of the present study was to determine and compare leaves, fruits, essential oil and the fatty acids of Laurus collected from three different geographic and climatic areas (Ras-Alnaqoura, Deir-El-Qamar and Zahle), and determine the genetic identity and the Genetic distance between these samples. A phytochemical test was done on different extracts prepared from dried leaves, using solvents of different polarities to determine Alkaloids, Flavonoids, Tannins, Anthraquinones and Coumarins. Moreover additional analytical experiments were applied on the samples to determine the Laurus composition of trace elements and showed that it was rich in K, Ca and Si. The highest percentages have been found in Deir-El-Qamar. The determination of fatty acids showed a high concentration in stearic, oleic, vaccenic and palmitic acids. we studied the genetic differences between the three samples of Laurus by ISSR (Inter Simple Sequence Repeat) technique, according to this study Laurus was classified into two major groups and two subgroups, the genetic distance between Deir-El-Qamar sample and other samples was about 70.80%, this result indicates a significant genetic diversity between the three regions.